Managing Learning Communities to Enhance Elementary Teacher Pedagogical Competence - Iwan Taryana; Hanafiah Hanafiah (Journal of Science and Education (JSE), 2026)
Enhancing teacher pedagogical competence is a cornerstone of educational quality improvement. Professional Learning Communities (PLCs) have emerged as a strategic model for fostering collaborative, sustained professional development. However, their implementation is often inconsistent, limiting their impact on classroom practice. This study aims to analyze the management processes underpinning the implementation of PLCs designed to improve the pedagogical competence of elementary school teachers. This research employed a qualitative approach with a multiple case study design conducted at two Indonesian public elementary schools: SDN Rawasirna and SDN Selajambe 1. Data were collected through in-depth interviews with principals and teachers, non-participant observations of PLC activities, and analysis of institutional documents. The data were analyzed using the interactive model of Miles and Huberman, involving cycles of data reduction, display, and conclusion drawing. The findings reveal that the management of PLCs was highly contextual. Planning was participatory, grounded in teachers' self-identified needs. Organization differed, with one school adopting a formal structure and the other a more flexible, emergent model. PLC activities evolved from simple discussions to collaborative inquiry, including lesson study and student work analysis. Oversight mechanisms, including principal supervision and peer feedback, were established to ensure accountability and reflection. The effective management of PLCs significantly contributed to enhancing teacher pedagogical competence. Success was contingent on transformative instructional leadership, a strong collaborative culture, and adaptive management of challenges such as time constraints and varying facilitator skills. The study concludes that the efficacy of PLCs is determined not by their mere existence but by the deliberate management of their planning, organization, implementation, and oversight processes.